2016
DOI: 10.1371/journal.pone.0149146
|View full text |Cite
|
Sign up to set email alerts
|

Bcl6 Is Required for Somatic Hypermutation and Gene Conversion in Chicken DT40 Cells

Abstract: The activation induced cytosine deaminase (AID) mediates diversification of B cell immunoglobulin genes by the three distinct yet related processes of somatic hypermutation (SHM), class switch recombination (CSR), and gene conversion (GCV). SHM occurs in germinal center B cells, and the transcription factor Bcl6 is a key regulator of the germinal center B cell gene expression program, including expression of AID. To test the hypothesis that Bcl6 function is important for the process of SHM, we compared WT chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…Additional experiments showed that Bcl6 transactivates Bach2 and targets the AICDA gene in cooperation with Pax5 (Alinikula et al, 2011). While Bcl6 not only transactivates AICDA, the activation of additional genes by Bcl6 are also required for Ig–gene conversion (Williams et al, 2016). Moreover, a Bach2 deficiency in the same cell line abrogated Ig–gene conversion and showed that Bach2 may transactivate the AICDA promoter as well as transactivate genes associated with function of the AID protein (Budzynska et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Additional experiments showed that Bcl6 transactivates Bach2 and targets the AICDA gene in cooperation with Pax5 (Alinikula et al, 2011). While Bcl6 not only transactivates AICDA, the activation of additional genes by Bcl6 are also required for Ig–gene conversion (Williams et al, 2016). Moreover, a Bach2 deficiency in the same cell line abrogated Ig–gene conversion and showed that Bach2 may transactivate the AICDA promoter as well as transactivate genes associated with function of the AID protein (Budzynska et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The ChIPs were done essentially as previously described (Williams et al, 2016), with the following modifications. 4 × 10 7 formaldehyde-fixed cells were lysed in SDS lysis buffer (50 mM Tris-HCl, pH 8.0, 10 mM EDTA, 1% SDS, supplemented with Complete, EDTA-free Protease Inhibitor Cocktail (Roche)) and diluted 4-fold with dilution buffer (16.4 mM Tris-HCl, pH 8.0, 167 mM NaCl, 1.2 mM EDTA, 0.01% SDS, 1.1% Triton X-100, supplemented with inhibitors).…”
Section: Chip-seqmentioning
confidence: 99%
“…We reasoned that immortalized DT40 cells overexpressing MYC would allow to more precisely dissect the roles of IRF4 and BLIMP‐1 in antibody secretion. This cell line is derived from chicken bursal follicles, where BCL6 and BACH2 are required for somatic hypermutation and gene conversion . We have previously shown that deletion of PAX5 or BCL6 in these cells leads to spontaneous upregulation of PRDM1 and differentiation into early ASC phenotype …”
Section: Introductionmentioning
confidence: 99%
“…This cell line is derived from chicken bursal follicles, where BCL6 and BACH2 are required for somatic hypermutation and gene conversion. 14,15 We have previously shown that deletion of PAX5 or BCL6 in these cells leads to spontaneous upregulation of PRDM1 and differentiation into early ASC phenotype. 4,16 In this study, we tested whether IRF4 is needed for antibody secretion and PRDM1 expression.…”
Section: Introductionmentioning
confidence: 99%